Psychological Interventions for Enhancing Marital Commitment: A Systematic Review - Wasono, Andy; Sugiharto, DYP; Nuzulia, Siti; Arinata, Firdian Setiya (KONSELOR, 2025)
Declining marital commitment weakens family stability and psychological health, increasing the need for evidence-based couple interventions. This systematic review consolidates empirical studies on psychological interventions aimed at strengthening marital commitment among married couples. Searches in Scopus, ProQuest, and Google Scholar covered publications from 2018 to 2025 using keywords related to marital commitment and psychological couple interventions. From 151 records, 15 duplicates were excluded, 136 titles and abstracts were screened, and 46 full texts were evaluated. Thirty-seven studies were discarded because they either did not measure marital commitment or did not meet design criteria. Seven studies met all the inclusion criteria. The methodological quality was assessed with the Mixed Methods Appraisal Tool. The diversity in study designs, formats, samples, and outcome measures precluded meta-analysis, so a narrative synthesis was conducted. Five categories of interventions were identified: cognitive-behavioural therapy (three studies), skills-based training in communication and conflict resolution (two randomised trials), acceptance and commitment therapy (one study), emotion-focused therapy (one study), and solution-focused brief therapy (one randomised trial). Cognitive-behavioural therapy and skills-based approaches showed the most consistent improvements in marital commitment, mainly through cognitive restructuring and enhanced communication. Acceptance-based and emotion-focused therapies showed some benefits but have limited replication; additionally, trials involving motivational interviewing were ineligible. Overall, current evidence most strongly supports cognitive-behavioural therapy and skills training. However, small sample sizes, short follow-up periods, and varied measures of commitment limit the ability to generalise findings, highlighting the need for large, longitudinal studies using standardised instruments across diverse cultural populations. Future research should focus on standardised commitment measures, transparent randomisation processes, and more extended follow-up periods beyond 12 months to evaluate long-term effectiveness and mechanisms across different contexts.